INDIAN CONSUMER: KING OR PAWN - Tatineni, Meher (South Asian Law Review Journal, 2019)
In a democracy, consumer welfare is the responsibility of the government as every citizen is a consumer in one way or another. In a competitive market, the consumer rights can be protected by evolving a network of legal instruments as well as an institutional mechanism to redress their grievances. In India the Consumer Protection Act, 1986 is the major social welfare legislation enacted to protect the consumers. Legislation has no doubt played a major role in protecting consumers but the available evidence suggests that even today the average Indian consumer remains exploited due to lack of awareness and consumer education. There is, therefore, a need to enhance consumer awareness and strengthen the consumer movement by involving various stakeholders.